Introduction to numerical methods with computer programming - Mukhopadhyay, Asok Kumar (Kalimata pus, 2005)
Introduction to numerical methods with computer programming / Mukhopadhyay, Asok Kumar. -- Kolkata: Kalimata pus., 2005 519.4 M957e3 3th ed. rev. No. of Copies : 1